SOCIALLY RESPONSIBLE CONSUMPTION IN THE CONDITIONS OF SHARPENING OF CONTRADICTION BETWEEN ARTIFICIAL AND NATURAL - Abysova, Maria (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Анотація. The article is devoted to the analysis of socially responsible consumption as a type of social responsibility, caused by the rapid growth of the technosphere, i.e. the integration of technology into society and culture. The concept of "technosphere" reflects the property of technology remaining in the form of local controlled objects creating an integrated environment. The current state of technogenic civilization can be called a crisis due to the displacement of the natural by the artificial. A technized society, as a quasinatural formation, perceives the standards of technical activity as a natural horizon for the development of events. A socially responsible consumption policy, opposed to the actions of commercial corporations pursuing financial and economic goals at the expense of public welfare, in particular in matters of environmental protection, and social stratification, declares itself as a form of civil and political action.